Numerical Study of Mechanical Properties in Honeycomb Sandwich Panels (Strojniški vestnik – Journal of Mechanical Engineering, 2016)
This research investigates the mechanical properties of honeycomb sandwich panels through numerical simulations. Load-bearing capacity, stiffness, and deformation characteristics were evaluated under various loading conditions. The findings support the application of lightweight composite structures in engineering.
Keywords: Honeycomb structures; Sandwich panels; Mechanical properties; Lightweight materials; Numerical simulation